Pengaruh Upah Minimum, Tingkat Pengangguran Terbuka, Pendidikan Dan Pengeluaran Pemerintah Terhadap Kemiskinan di Indonesia - Erliza Millenia Putri; Dewi Zaini Putri (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2021)
This study aims to determine and analyze the effect of the minimum wage, open unemployment rate, education and government spending on poverty in Indonesia. This research is a kind of descriptive and inductive research. The data used is secondary panel data from 2010-2019 obtained from related institutions and then analyzed using a panel data regression model by performing a classical assumption test. The results of this study indicate that: (1) the minimum wage has a positive and insignificant effect on poverty, (2) the open unemployment rate has a positive and insignificant effect on poverty, (3) education has a negative and significant effect on poverty, and (4) government spending has a negative effect and not significant on poverty in Indonesia.